Monitoring Perparkiran Mobil Berbasis Sensor Ultrasonik dan Mikrokontroller ESP8266 - Nur, Dahlia; Pradana, Yori Putra; Kadir, Sahbuddin Abdul (INTEK: Jurnal Penelitian, 2019)
— The number of motorized vehicles in Indonesia is increasing rapidly every year. Based on data from the Central Statistics Agency (BPS) in 2017, the number of motorized vehicles with Passenger Car vehicles reached 15,493,068 units. The number has increased compared to 2016 amounted to 14,580,666 units. The increase as the number of motorized vehicles has an impact of the availability of parking lots in a number of locations. Every driver who will park the vehicle wants to get the location / lot of the parking lot as soon as possible. However, the unavailability of parking capacity information in a parking area causes the user to go around first to get an unload parking space, if the parking lot is full, the user even has to go back out because he did not get a parking space. This study designed and built an ESP8266 microcontroller and PING ultrasonic sensor provided information about the availability of parking lots were still unoccupied in this monitoring system. It is hoped can improve the efficiency of parking users who are looking for vacant parking lots and make it easier for parking admins in parking monitoring management. The results showed that the monitoring system that was built could provide information about the availability of empty parking lots and integrated databases to store vehicle owner information based on parking cards. Parking lot information is included on the parking card given to users entering the parking area.